Berpikir ulang tentang keindonesiaan - Oetama, Jakob, 1931- (Jakarta : Kompas, 2001)
Essays on political issues and social condition in Indonesia; collected articles
Keywords: Indonesia -- Politics and government; Indonesia -- Social aspects